Student Knowledge on Food Additives: Do They Really Care? - Jamaluddin, Rahimah; Mohamed, Suriani; Ismail, Sarimah; Kamis, Arasinah; Zakaria, Anis (International Journal of Psychosocial Rehabilitation, 2020)
For centuries, food additives have proven to be beneficial in a variety of foods. Consumers demand and enjoy a food supply that is flavorful, nutritious, safe, convenient, colourful and affordable. However, excessive intake of food additives can harm the body in many ways. The main goal of this study was to identify student knowledge on food additives, the risks of taking food with additives and examine their food intake practice. This study involved 187 students who attended various fields of study at Universiti Putra Malaysia. Questionnaires in the form of a quantitative survey were distributed to the sampel. Findings showed that students' knowledge on food additives was at a moderate level with a mean value of 2.47 (SD.59), meanwhile mean for student knowledge on risk of taking food additives was3.90 (0.91). Findings also showed that the mean value for frequency of food consumption within the period of six months among the students was low with of 2.69, (SD .90). This finding indicates that students are consuming food with additives continously regardless of having knowledge about the risk of taking it. There is a need to take into consideration to strengthen students’ knowledge on healthy food intake for a better life in future.